(untitled) (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2022)
The fermentation of cocoa beans is a key step in increasing their quality. Temperature and pH have an impact on the fermentation process’ performance. Until, temperature and pH measurements in the cocoa bean fermentation process have been done with a thermometer and a pH meter, and have been heavily impacted by experience and knowledge. The goal of this research is to create a temperature and pH monitoring system for the fermentation of cocoa beans using an android platform. The sensor must be able to measure temperature and pH during the fermentation process, and the sensor reading data must be displayed on the android display, according to the system design criteria. A temperature sensor, pH sensor, microcontroller, TP-Link or WiFi modem, ThingSpeak (data storage), and Smartphone make up the system’s hardware. Arduino CC software version 1.8.14 was used to create the software. The system hardware was made up of numerous components, including the NodeMCU ESP32 microcontroller, SKU SEN0161 pH sensor, DS18B20 temperature sensor, 4.2k resistor, jumper cable, and 5 volt charger adaptor, according to the results. A plastic container houses the electronic system circuit. The monitoring system can read the temperature and pH during the fermentation process, which lasts 112 hours or 6 days, according to the performance test findings. During fermentation, the temperature of cocoa beans ranged from 27.19 Â°C to 41.75 Â°C, with the pH fluctuating between 2.50 and 7.10.